2018
DOI: 10.1039/c8py00484f
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-based nanocomposites for heavy metal ions removal from aqueous solution: a review

Abstract: A review of versatile polymer-based composites containing different functional organic and/or inorganic counterparts for the removal of hazardous metal ions from wastewater solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
159
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(162 citation statements)
references
References 173 publications
1
159
0
2
Order By: Relevance
“…To reduce the problem of environmental pollution, the scientists have anticipated using very low cost and the natural biodegradable polymer such as cellulose which can be transformed to accomplish high ability eliminate of the metals cation. This is because bio‐polymer adsorbents have prefect skeleton strength, easy modified surface functional unit feasible and eco‐friendly which is high expectation for application as a adsorbent …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the problem of environmental pollution, the scientists have anticipated using very low cost and the natural biodegradable polymer such as cellulose which can be transformed to accomplish high ability eliminate of the metals cation. This is because bio‐polymer adsorbents have prefect skeleton strength, easy modified surface functional unit feasible and eco‐friendly which is high expectation for application as a adsorbent …”
Section: Introductionmentioning
confidence: 99%
“…Cellulose‐based adsorbent from biomass is widely used due to it have good swelling resistance in different solvent, high mechanical strength, relatively low density and large surface area, and high specific strength that allow the production of low‐density composites with high filler content ,. In order to further improve the adsorption performance of bio‐polymeric adsorbent, surface functionalization of polymers to obtain bio‐polymer‐based composites is considered as an effective method on the initial of that the incorporated functional counterparts would provide more interesting interaction with the target metal cation . Among all the method to cellulose remodeling, the simplest and easy operating procedure can be used which the backbone of the cellulose can be adapted with metals cation attaching functional groups or chelating bonded with the first or alternate hydroxyl groups of an anhydrous‐glucose unit (AGU).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are also reported in literature for heavy metal removal using polymer based nanocomposites . However, because of demerits such as limited adsorption capacity and larger quantity of adsorbents required limits their use.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that FRP is a metal‐free process, it can be an environmentally friendly synthetic strategy to prepare useful adsorbents for heavy metal ion removal. Moreover, to the best of our knowledge, the direct synthesis of sulfur‐containing nanoporous adsorbents via FRP is still a great challenge . Keeping this idea in perspective, in this work, we report a facile polymerization‐cutting strategy to synthesize thiol‐based cross‐linked nanoporous adsorbents for efficient mercury removal from water.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Considering that FRP is am etal-free process, it can be an environmentally friendlys ynthetic strategyt op repare usefula dsorbents for heavy metal ion removal.M oreover,t o the besto fo ur knowledge,t he direct synthesis of sulfur-containingn anoporous adsorbentsv ia FRP is still ag reat challenge. [26] Keepingt his idea in perspective,i nt his work, we report af acile polymerization-cutting strategy to synthesize thiol-based cross-linked nanoporous adsorbentsf or efficient mercury removal from water.T he proposedm ethodology allows ad irectf ree-radical polymerizationo fd ivinyl disulfide derivative( bis-(4-vinylbenzyl)-disulfide) with divinylbenzene (DVB) as ac o-crosslinker to form the disulfide and DVB cocrosslinked nanoporous adsorbents (NAs-SS). Then, the disulfide linkage in the backbone can be easily cut off and reduced to thiol groupsw ithin the networks (Scheme1).…”
Section: Introductionmentioning
confidence: 99%